Prevalence of hypertension and its associated risk factors among teachers in governmental secondary schools of Godawari Municipality, Lalitpur: a cross-sectional study - Ghimire, Nirmala; Mishra, Rachana (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Hypertension is one of the leading causes of premature morbidity and mortality in the world and prevalence is rising in developing countries. The objective of this study was to determine the prevalence and the associated risk factors among teachers working in governmental secondary schools in Godawari Municipality, Lalitpur, Nepal.Method: A cross-sectional analytical study was conducted among the teachers working in the governmental secondary schools during June to August 2023. Sample size was 309 (total enumerative sampling). Data was collected by using a self-administered questionnaire and conducting physical measurements. Chi square test was used to assess the factors associated with hypertension. Multiple logistic regression analysis was done to find out the risk factors of hypertension.Result: Among 309 participant, 165(53.40%) were female, 186(60.19%) were above 40 years of age.The prevalence of hypertension was 89(28.80%) among which 48(53.93%) participants were already diagnosed as hypertension and on medication. The prevalence of hypertension was positively associated (p < 0.05) with age, co-morbid condition, family history of hypertension, smoking and alcohol consumption habit, dietary patterns, body mass index, physical activity and obesity. The multivariate logistic regression analysis identified age, smoking habit and alcohol consumption as risk factors for the development of hypertension among the schoolteachers.Conclusion: From the findings of the study, it is concluded that the prevalence of hypertension among schoolteachers is 28.8. Awareness program including lifestyle modification and behavior change is important for the prevention and treatment of hypertension among these teachers.